A method for synthesizing nitrogen-doped tungsten trioxide catalyst for complete photolysis of water
Through the synthesis method of nitrogen-doped tungsten trioxide, the existing photohydrolysis catalyst has been solved, the problems of low efficiency, scarce raw materials and poor photocorrosion are achieved, and the preparation of photohydrolysis catalysts is achieved, which is suitable for scale Chemical production.
Patent Information
- Application Number
- CN202311130596.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-21
- Filing Date
- 2023-09-01
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-09-01
AI Technical Summary
The existing complete photohydrolysis catalyst has low efficiency, scarce raw materials and high cost, the obtained photocatalyst has poor photocorrosion resistance, short service life, and cumbersome and complex synthesis methods, which is not conducive to large-scale preparation.
The synthesis method of nitrogen-doped tungsten trioxide is used to control the morphology and size of the nanostructure through different molar ratios of sodium tungstate and hydroxylamine hydrochloride. Combined with carbon paper or carbon fiber paper as a carrier, nitrogen with a graded nanostructure is formed. Doped with tungsten trioxide photocatalyst.
It significantly improves the activity and service life of the photohydrolysis catalyst, reduces costs, and achieves efficient conversion efficiency from solar energy to hydrogen, which is suitable for large-scale production.
Smart Images

Figure CN117160512B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a metal oxide complete photolysis water catalyst, in particular to a method for synthesizing a nitrogen-doped tungsten trioxide complete photolysis water catalyst. Background Art
[0002] Given the huge reserves of water on Earth and its clean renewability, low-cost complete photocatalytic water splitting to produce hydrogen will become one of the most effective hydrogen suppliers, making it a focus of attention in the production of hydrogen energy and hydrogen raw materials. The efficiency and feasibility of complete photocatalytic water splitting to produce hydrogen depends on the activity of the photocatalyst and the cost of the materials, especially the appropriate electronic structure required for complete water splitting (i.e., the bottom of the conduction band is more negative than the hydrogen evolution potential and the top of the valence band is more positive than the oxygen evolution potential) and the narrowest possible band gap ensures a wider solar spectrum absorption range. Therefore, the development of a synthesis method for a complete photocatalytic water splitting catalyst with high activity, stable structure, simple synthesis process, low cost, and scalable preparation plays a decisive role in achieving efficient photocatalytic water splitting to produce hydrogen.
[0003] At present, the method of producing hydrogen from water by photolysis by adding sacrificial reagents, electron mediators, and external bias voltage is much more expensive than hydrogen produced by fossil fuels due to the use of external reagents or auxiliary equipment, and cannot be applied and promoted in practice. Although there are many experimental methods for synthesizing complete photocatalytic water splitting, the apparent quantum yield (AQE) of hydrogen evolution is extremely low (<1%); or the raw materials used are scarce and costly (for example: rare metal element compounds such as gallium and indium, and expensive precious metals such as rhodium and platinum must be used as co-catalysts), and the synthesis method is cumbersome and complicated, and the obtained catalysts are severely photocorroded, have poor structural stability, and have a short service life, which cannot meet the requirements of large-scale practical applications. The current research on complete photocatalytic water splitting is still far from the practical application of photocatalytic water splitting and large-scale catalyst synthesis, so photocatalytic water splitting cannot replace the currently widely used fossil fuel hydrogen production. Furthermore, the conduction band bottom of the currently synthesized nanostructured tungsten oxide photocatalyst is more positive than the water reduction hydrogen evolution potential, and is only suitable for the oxygen evolution half reaction of photoelectrochemical water splitting under applied bias voltage (see Y. Liu, et al., Adv.Energy Mater .2016, 6 , 1600437. W. Li, et al., ACS Nano 2014, 8 , 11770–11777. G. Wang, et al., Energy Environ. Sci .2012, 5, 6180–6187.), but cannot achieve complete photocatalytic water splitting. However, the low raw material price and synthesis cost of tungsten oxide catalysts, the inherent ultra-high thermal catalytic activity of hydrogen and oxygen evolution, good structural stability, excellent light corrosion resistance, and ultra-long service life are undoubtedly more able to meet the needs of industrial-scale photocatalytic water splitting. By combining appropriate heteroatom doping with nanostructure design and manufacturing, the composition and nanostructure of tungsten oxide photocatalysts (high active surface area and short photogenerated carrier transmission distance) are regulated to obtain the appropriate electronic structure and advanced nanostructure for complete water splitting, thereby significantly improving its activity, realizing the innovation of complete photocatalytic water splitting, and thus reducing the preparation cost of green hydrogen.
[0004] To this end, it is necessary to explore a suitable doping method to synthesize nanostructured tungsten oxide catalysts and regulate the composition, and then establish a low-cost and reliable synthesis process route to facilitate mass production and ensure stable product quality. This is of great significance for promoting the development of zero-carbon hydrogen production by complete photolysis of water and meeting the low-cost, green, sustainable and safe requirements of the hydrogen production industry. Summary of the invention
[0005] 1. Technical problems to be solved:
[0006] Most existing complete photocatalytic water splitting catalysts have low efficiency (solar energy → hydrogen (STH) conversion efficiency is less than 1%), and the raw materials used for high-activity photocatalysts are scarce and expensive. The resulting photocatalysts have poor light corrosion resistance and a short service life, and the synthesis method is cumbersome and complex, which is not conducive to large-scale preparation.
[0007] 2. Technical solution:
[0008] In order to solve the above problems, the present invention provides a method for synthesizing a nitrogen-doped tungsten trioxide complete photolysis water catalyst, comprising the following steps:
[0009] Step 1: Sodium tungstate (Na 2 WO 4 ·2H 2 O) and hydroxylamine hydrochloride are fully dissolved in a mixed solvent of water and glacial acetic acid to obtain a solution, wherein the concentrations of sodium tungstate and hydroxylamine hydrochloride in the solution are 0.01 to 1 mol L −1 and 0.0025 ~ 4 mol L −1 , maintaining the molar ratio of sodium tungstate to hydroxylamine hydrochloride in the solution at 1:0.25-4.00, and then transferring to an autoclave reactor.
[0010] Step 2: immerse 4 to 6 pieces of surface hydroxylated carbon paper or carbon fiber paper treated with 68 to 70% concentrated nitric acid at 70 to 80°C for 1.5 to 2.5 hours in the reactant solution of the autoclave reactor, seal the reactor and heat it to 120 to 220°C for 5 to 25 hours, cool the reactor to room temperature and release the pressure, take out the carbon paper or carbon fiber paper covered with nitrogen-doped tungsten trioxide with hierarchical nanostructure from the autoclave, wash it thoroughly with warm water at 40 to 45°C for 2 to 4 times, and dry it at 55-65°C.
[0011] Step 3: Then, the nitrogen-doped tungsten trioxide carbon paper or carbon fiber paper obtained in step 2 is placed in a vacuum at 4~6℃ min −1 The temperature is raised to 300-400°C and annealed at this temperature for 1.5-2.5 hours to obtain nitrogen-doped tungsten trioxide which is firmly bonded to carbon paper or carbon fiber paper and has improved crystallinity.
[0012] When the molar ratio of sodium tungstate to hydroxylamine hydrochloride is 1:0.25~0.4, the obtained hierarchical nanostructured nitrogen-doped tungsten trioxide photocatalyst is a hierarchical structured nanoneedle sea urchin-like cluster, and the loading amount of nitrogen-doped tungsten trioxide on the carbon paper or carbon fiber paper substrate is 2~30 mg cm ‒2 , denoted as N-WO 3 −I photocatalyst; when the molar ratio of sodium tungstate to hydroxylamine hydrochloride is 1:0.5~1.1, the obtained hierarchical nanostructured nitrogen-doped tungsten trioxide photocatalyst is a spherical cage-like cluster of mutually coiled nanobelts, and the loading amount of nitrogen-doped tungsten trioxide on the carbon paper or carbon fiber paper substrate is 2~30 mg cm ‒2 , denoted as N-WO 3 −II; when the molar ratio of sodium tungstate to hydroxylamine hydrochloride is 1:1.2~2.1, the obtained hierarchical nanostructured nitrogen-doped tungsten trioxide photocatalyst is a nanobelt spherical cluster, and the loading amount of nitrogen-doped tungsten trioxide on the carbon paper or carbon fiber paper substrate is 2~30mg cm ‒2 , denoted as N-WO 3 −III; when the molar ratio of sodium tungstate to hydroxylamine hydrochloride is 1:2.2~4.0, the obtained hierarchical nanostructured nitrogen-doped tungsten trioxide photocatalyst is a comb-shaped nanobelt spherical cluster, and the loading amount of nitrogen-doped tungsten trioxide on the carbon paper or carbon fiber paper substrate is 2~30 mg cm ‒2 , denoted as N-WO 3 −IV.
[0013] The area of the prepared integrated nitrogen-doped tungsten trioxide carbon paper or carbon fiber paper photocatalyst panel is 1 × 3 ~25 × 25 cm 2 .
[0014] The N-WO 3 The size of the primary urchin-like nanoneedle clusters of the −I photocatalyst is 7 ~ 10 μm, the diameter of the secondary nanoneedles is 30 ~ 50 nm, and the atomic ratio of nitrogen to tungsten is 1:50 ~ 25.
[0015] The N-WO 3 The size of the primary cage-like nanobelt clusters of the −II photocatalyst is 7 ~ 12 μm, the width and thickness of the secondary nanobelts are 20 ~ 30 nm and 5 ~ 10 nm, respectively, and the atomic ratio of nitrogen to tungsten is 1:24 ~ 15.
[0016] The N-WO 3 The thickness and length of the −III photocatalyst nanobelts are 5 ~ 10 nm and 1 ~ 2 μm, respectively, and the atomic ratio of nitrogen to tungsten is 1:14 ~ 6.6.
[0017] The N-WO 3 The thickness and length of the −IV photocatalyst nanobelts are 5 ~ 10 nm and 1 ~ 2 μm, respectively, and the atomic ratio of nitrogen to tungsten is 1:6.5 ~ 4.5.
[0018] The N-WO 3 The light absorption starting wavelength of the −I photocatalyst is 460-470 nm, and the solar energy → hydrogen conversion efficiency is 0.5% ~ 1.6%.
[0019] The N-WO 3 The light absorption starting wavelength of the −II photocatalyst is 475-485 nm, and the apparent quantum efficiency of complete photolysis of water is 1.6% ~ 2.5%.
[0020] The N-WO 3 The light absorption starting wavelength of the −III photocatalyst is 485-495 nm, and the apparent quantum efficiency of complete photolysis of water is 2.5% ~ 3.1%.
[0021] The N-WO 3 The light absorption starting wavelength of the −IV photocatalyst is 490-500 nm, and the apparent quantum efficiency of complete photolysis of water is 3.1% ~ 4.0%.
[0022] In step 1, the volume ratio of water to glacial acetic acid is 1:0.9-1.1.
[0023] In step 1, the volume of the autoclave reactor is 1.125 to 2.5 times the volume of the solution and is lined with polytetrafluoroethylene.
[0024] The material of the autoclave reactor is stainless steel.
[0025] 3. Beneficial effects:
[0026] Compared with the prior art, the synthesis method of the complete photocatalytic water splitting catalyst provided by the present invention has the following advantages: due to the formation of a unique hierarchical nanostructure and a small-sized secondary structure, the specific surface area (number of active sites) and scattering light ability of the photocatalytic water splitting catalyst are improved, the light absorption ability and catalytic activity are enhanced, and the amount of catalyst used is saved; the highly porous carbon (fiber) paper substrate promotes the diffusion and mass transfer of water molecules to the surface of the photocatalyst; nitrogen is doped into the tungsten trioxide lattice, the electronic structure is improved, and an energy band structure that perfectly matches the water redox potential is obtained; the small-sized secondary nanostructure significantly reduces the transmission distance of the photogenerated carriers, and greatly avoids the recombination of charges; the inherent ultra-high hydrogen and oxygen evolution thermal catalytic activity of tungsten atoms increases the water decomposition rate; good structural stability and excellent light corrosion resistance; the high earth abundance of tungsten elements ensures the low raw material price and synthesis cost of tungsten oxide catalysts. The above characteristics significantly improve the activity of the complete photocatalytic water splitting catalyst (the maximum conversion efficiency of solar energy to hydrogen (STH) can reach 3.8%), the service life, and reduce its cost price. The addition of the carbon (fiber) paper carrier leads to the direct formation of an integrated complete photocatalytic water splitting catalyst panel after the reaction is completed. The photocatalyst is evenly distributed to avoid aggregation, ensuring sufficient contact with water and easy separation of the photocatalyst from water; the primary and secondary structure size distribution range of the photocatalyst is narrow, and the shape of the graded nanostructure is uniform, ensuring the stability and repeatability of the catalytic performance; the size of the carbon (fiber) paper carrier in this reaction route is adjustable, and the photocatalytic panel can be scaled up and the quality is stable. The above advantages lay the foundation for the application of this preparation method in low-cost large-scale green hydrogen production. Therefore, the preparation method of the nitrogen-doped tungsten trioxide / carbon (fiber) paper complete photocatalytic water splitting catalyst panel provided by the present invention is suitable for large-scale production and has a very broad market prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is N-WO prepared in Example 1 of the present invention. 3 (A) Low magnification scanning electron microscopy (SEM), (B) medium magnification scanning electron microscopy (SEM) (inset: high magnification scanning electron microscopy (SEM)), and (C) transmission electron microscopy (TEM) images of N-WO photocatalyst. (D) X-ray diffraction (XRD) pattern. (E) X-ray photoelectron spectroscopy full scan pattern, (F) tungsten 4f and (G) nitrogen 1s high resolution spectra. (H) UV-visible near-infrared absorption spectrum obtained by UV-visible diffuse reflectance spectroscopy (absorption in the long-wave range comes from N-WO 3 localized surface plasmon resonance effect).
[0028] Figure 2It is N-WO prepared in Example 2 of the present invention. 3 (A) Low magnification scanning electron microscopy (SEM), (B) medium magnification scanning electron microscopy (SEM), and (C) transmission electron microscopy (TEM) images of N-WO-II photocatalyst (inset: high magnification scanning electron microscopy (SEM) image). (D) X-ray diffraction (XRD) pattern. (E) X-ray photoelectron spectroscopy full scan pattern, (F) tungsten 4f and (G) nitrogen 1s high resolution spectra. (H) UV-visible near-infrared absorption spectrum obtained by UV-visible diffuse reflectance spectroscopy (absorption in the long-wave range comes from N-WO 3 localized surface plasmon resonance effect).
[0029] Figure 3 It is N-WO prepared in Example 3 of the present invention. 3 −III photocatalyst (A) low magnification scanning electron microscopy (SEM), (B) medium magnification scanning electron microscopy (SEM), (C) transmission electron microscopy (TEM) (inset: high magnification scanning electron microscopy (SEM)), and (D) high-resolution transmission electron microscopy (HRTEM) images (the planes with spacings of 3.643 Å and 3.795 Å in the figure are attributed to the hexagonal structure of N-WO, respectively) 3 (110) and (002) lattice planes). (E) X-ray diffraction (XRD) pattern. (F) X-ray photoelectron spectroscopy full scan pattern, (G) tungsten 4f and (H) nitrogen 1s high resolution patterns. (I) N 2 (77.4K) adsorption-desorption isotherms. (J) UV-visible near-infrared absorption spectra obtained by UV-visible diffuse reflectance spectroscopy (the absorption in the long-wave range comes from N-WO 3 localized surface plasmon resonance effect).
[0030] Figure 4 It is N-WO prepared in Example 4 of the present invention. 3 (A) Low magnification scanning electron microscopy (SEM), (B) medium magnification scanning electron microscopy (SEM), (C) transmission electron microscopy (TEM) (inset: high magnification scanning electron microscopy (SEM)), and (D) high-resolution transmission electron microscopy (HRTEM) images of the −IV photocatalyst (the planes with spacings of 3.637 Å and 3.156 Å in the figure are assigned to the hexagonal structure of N-WO, respectively 3(110) and (220) lattice planes). (E) Energy dispersive X-ray spectroscopy (TEM-EDX) image, (F) SEM-EDX element distribution image. (G) X-ray diffraction (XRD) pattern. (H) X-ray photoelectron spectroscopy full scan pattern, (I) tungsten 4f and (J) nitrogen 1s high resolution spectra. (K) N 2 (77.4 K) Adsorption-desorption isotherms. (L) UV-visible near-infrared absorption spectra obtained by UV-visible diffuse reflectance spectroscopy (the absorption in the long-wave range comes from N-WO 3 localized surface plasmon resonance effect).
[0031] Figure 5 The various N-WO prepared in Examples 1-4 of the present invention 3 Photocatalyst (A) photocatalyzes H 2 With O 2 The precipitation amount and molar ratio of pure water change with time (data point: red, N-WO 3 −IV; blue, N-WO 3 −III; cyan, N-WO 3 −II; black, N-WO 3 −I), (B) Under simulated solar irradiation, H 2 With O 2 Photo of precipitation from pure water, (C) N-WO 3 −III catalytic hydrogen production apparent quantum efficiency (AQE) for complete decomposition of pure water as a function of irradiation wavelength and the corresponding UV−visible near-infrared absorption spectra, (D) N-WO 3 The apparent quantum efficiency (AQE) of hydrogen production from the complete decomposition of pure water by −IV catalysis varies with the irradiation wavelength and the corresponding UV−visible near-infrared absorption spectra. A 300 W xenon lamp equipped with various bandpass filters was used to test the apparent quantum efficiency (AQE).
[0032] Figure 6 (A) N-WO prepared in Examples 1-4 of the present invention 3 −IV, (B) N-WO 3 −III, (C)N-WO 3 −II, and (D)N-WO 3 −I photocatalyst measured in air photoelectron spectra (PESA), thereby obtaining the maximum value at the top of the valence band of each photocatalyst. (E) Various N-WO 3 Photocatalysts through ( αhv ) 0.5 and photon energy ( hv ) relationship curve to obtain the band gap energy ( E g) value (curve: red, N-WO 3 −IV; blue, N-WO 3 −III; cyan, N-WO 3 −II; black, N-WO 3 −I). (F) Various N-WO 3 The band gap energy of the photocatalyst ( E g ), the energy level positions of the conduction band bottom minimum (CBM) and the valence band top maximum (VBM) (left, N-WO 3 −IV; middle left, N-WO 3 −III; middle right, N-WO 3 −II; right, N-WO 3 −I), and the redox potential position of water splitting. DETAILED DESCRIPTION
[0033] The present invention is described in detail below with reference to the accompanying drawings and embodiments.
[0034] Example 1
[0035] A method for synthesizing a catalyst for photolysis of water by using nitrogen-doped tungsten trioxide with hierarchical nanostructures, comprising the following steps: dissolving 0.132 to 13.195 g of sodium tungstate dihydrate in 20 ml of water, then adding an equal volume of glacial acetic acid and mixing them thoroughly, and then adding 0.007 to 0.695 g of hydroxylamine hydrochloride, wherein the concentration of sodium tungstate is 0.01 to 1 mol L −1 , Hydroxylamine hydrochloride concentration: 0.0025 ~ 0.25 mol L −1 , and the molar ratio of sodium tungstate to hydroxylamine hydrochloride is maintained at 1:0.25. The reaction mixture is then transferred to a 50 ml stainless steel autoclave reactor lined with polytetrafluoroethylene, and 4 to 6 pieces of carbon paper or carbon fiber paper (1 × 3 ~ 5 × 5 cm) treated with concentrated nitric acid at a concentration of 68 to 70% at 75°C for 2 hours are placed. 2 ) is immersed in the reactant solution in the autoclave reactor, sealed and heated to any temperature in the range of 150 ℃ ~ 220 ℃, reacted for 12 hours, and then cooled to room temperature. The carbon paper or carbon fiber paper covered with nitrogen-doped tungsten trioxide is taken out, washed three times in warm water at 40 ~ 45 ℃, and then dried for use. Thus, nitrogen-doped tungsten trioxide nanoneedle sea urchin-like clusters with hierarchical nanostructures, namely N-WO 3 −I catalyst. Hydroxylamine hydrochloride is not only a nitrogen source, but also can effectively control the morphology and size of the hierarchical nanostructured nitrogen-doped tungsten trioxide. The size of the primary clusters is 7 ~ 10 μm, and the diameter of the secondary nanoneedles is 30 ~ 50 nm.
[0036] N-WO prepared in Example 1 3 −I SEM of photocatalyst, such as Figure 1 A. Figure 1 As shown in B, Figure 1 The TEM image shown in C shows that when the molar ratio of sodium tungstate to hydroxylamine hydrochloride is 1:0.25, N-WO 3 −I has the morphology of hierarchical nanoneedle sea urchin-like clusters, such as Figure 1 The XRD pattern shown in D confirms that N-WO 3 −I has the same 3 The same hexagonal structure, such as Figure 1 The XPS full scan shown in E is similar to that shown in Figure 1 F and Figure 1 The high-resolution spectrum of the elements shown in G shows that N-WO 3 −I is composed of W, O, and N elements, and the atomic ratio of W / O / N is 24.8:74.2:1.0, such as Figure 1 The UV-visible-near infrared absorption spectrum shown in H shows the onset absorption wavelength of the band gap transition (λ onset ) is about 466 nm, and there is localized surface plasmon resonance absorption at long wavelengths. Specific surface area ( S BET ) is 26.4 m 2 g ‒1 .
[0037] like Figure 5 As shown in A, N-WO prepared in Example 1 above 3 The average rates of hydrogen and oxygen evolution over the photocatalyst were 0.00862 mmol h −1 and 0.00430 mmol h −1 , the ratio of hydrogen evolution to oxygen evolution rate is 2.00. The conversion efficiency of solar energy to hydrogen (STH) for complete photolysis of water is 1.6%. The maximum value of the valence band top (VBM) measured by photoelectron spectroscopy (PESA) is 6.63 eV, such as Figure 6 D, the N-WO was calculated by UV-visible near-infrared absorption spectroscopy. 3 −I Band gap energy of photocatalyst ( E g ) is 2.86eV, such as Figure 6 E, according to the band gap energy ( E g ) and the maximum value of the valence band top (VBM), the minimum value of the conduction band bottom (CBM) is calculated to be 3.77 eV, that is, the potentials of the maximum value of the valence band top (VBM) and the minimum value of the conduction band bottom (CBM) relative to the standard hydrogen electrode are 2.19 V and −0.67 V, respectively, which meet the thermodynamic potential requirements for complete water decomposition, such as Figure 6 As shown in F.
[0038] Example 2
[0039] A method for synthesizing a hierarchical nanostructured nitrogen-doped tungsten trioxide catalyst for complete photocatalytic water splitting comprises the following steps: 0.132 to 13.195 g of sodium tungstate dihydrate is fully dissolved in 20 ml of water, then an equal volume of glacial acetic acid is added for thorough mixing, and then 0.028 to 2.780 g of hydroxylamine hydrochloride is added, and the sodium tungstate concentration is 0.01 to 1 mol L −1 , Hydroxylamine hydrochloride concentration: 0.01 ~ 1 mol L −1 , and the molar ratio of sodium tungstate to hydroxylamine hydrochloride is maintained at 1:1. The reaction mixture is then transferred to a 50 ml stainless steel autoclave reactor lined with polytetrafluoroethylene, and 4 to 6 pieces of carbon paper or fiber paper (1 × 3 ~ 5 × 5 cm) treated with concentrated nitric acid at a concentration of 68 to 70% at 75 °C for 2 hours are placed. 2 ) is immersed in the reactant solution in the autoclave reactor, sealed and heated to any temperature in the range of 150 ℃ ~ 220 ℃, reacted for 12 hours, and then cooled to room temperature. The carbon paper or fiber paper covered with nitrogen-doped tungsten trioxide is taken out, washed three times in warm water at 40 ~ 45 ℃, and then dried for use. Thus, nitrogen-doped tungsten trioxide with hierarchical nanostructures, intertwined nanobelt spherical cage clusters, namely N-WO 3 −II catalyst. Hydroxylamine hydrochloride is not only a nitrogen source, but also can effectively control the morphology and size of the hierarchical nanostructured nitrogen-doped tungsten trioxide. The size of the primary cage clusters is 7 to 12 μm, and the width and thickness of the secondary nanobelts are 20 to 30 nm and 5 to 10 nm, respectively.
[0040] N-WO prepared in Example 2 3 −II SEM of photocatalyst, such as Figure 2 A and Figure 2 B, and Figure 2 From the TEM image of C, it can be seen that when the molar ratio of sodium tungstate to hydroxylamine hydrochloride is 1:1, N-WO 3 −II has the morphology of spherical cage-like clusters of hierarchical nanoribbons, XRD patterns, such as Figure 2 As shown in D, it is confirmed that N-WO 3 −II has the same 3 The same hexagonal structure, such as Figure 2 The XPS full scan shown in E is Figure 2 F and Figure 2 The high-resolution spectrum of the elements shown in G shows that N-WO 3−II is composed of W, O, and N elements, with the atomic ratio of W / O / N being 25.6:72.7:1.7, and the UV−visible near-infrared absorption spectrum, e.g. Figure 2 H shows the onset absorption wavelength of the band gap transition (λ onset ) is about 480 nm, and there is localized surface plasmon resonance absorption at long wavelengths. S BET ) is 29.1 m 2 g ‒1 .
[0041] like Figure 5 As shown in A, N-WO prepared in Example 2 above 3 The average rates of hydrogen and oxygen evolution over the photocatalysts were 0.0316 mmol h −1 and 0.0156 mmol h −1 , the ratio of hydrogen evolution rate to oxygen evolution rate is 2.03, such as Figure 5 A. The conversion efficiency of solar energy to hydrogen (STH) for complete photolysis of water is 2.5%. The maximum value (VBM) of the valence band top measured by photoelectron spectroscopy (PESA) is 6.42 eV, as shown in Figure 6 C, the N-WO was calculated by UV-visible near-infrared absorption spectroscopy. 3 −II band gap energy of photocatalyst ( E g ) is 2.84 eV, such as Figure 6 E, according to the band gap energy ( E g ) and the maximum value of the valence band top (VBM), the minimum value of the conduction band bottom (CBM) is calculated to be 3.58 eV, that is, the potentials of the maximum value of the valence band top (VBM) and the minimum value of the conduction band bottom (CBM) relative to the standard hydrogen electrode are 1.98 V and −0.85 V, respectively, which meet the thermodynamic potential requirements for complete water decomposition, as shown in Figure 6 As shown in F.
[0042] Example 3
[0043] A method for synthesizing a hierarchical nanostructured nitrogen-doped tungsten trioxide catalyst for complete photocatalytic water splitting comprises the following steps: 0.132 to 13.195 g of sodium tungstate dihydrate is fully dissolved in 20 ml of water, then an equal volume of glacial acetic acid is added for thorough mixing, and then 0.056 to 5.560 g of hydroxylamine hydrochloride is added, and the sodium tungstate concentration is 0.01 to 1 mol L −1 , Hydroxylamine hydrochloride concentration: 0.02 ~ 2 mol L −1, and the molar ratio of sodium tungstate to hydroxylamine hydrochloride is maintained at 1:2. The reaction mixture is then transferred to a 50 ml stainless steel autoclave reactor lined with polytetrafluoroethylene, and 4 to 6 pieces of carbon paper and fiber paper (1 × 3 to 5 × 5 cm) treated with concentrated nitric acid at a concentration of 68 to 70% at 75°C for 2 hours are placed. 2 ) is immersed in the reactant solution in the autoclave reactor, sealed and heated to any temperature in the range of 150℃ ~ 220℃, reacted for 12 hours, and then cooled to room temperature. The carbon paper and carbon fiber paper covered with nitrogen-doped tungsten trioxide are taken out, washed three times in warm water at 40 ~ 45℃, and then dried for use. Thus, nitrogen-doped tungsten trioxide nanobelt spherical clusters with hierarchical nanostructures, namely N-WO 3 −III catalyst. Hydroxylamine hydrochloride is not only a nitrogen source, but also can effectively control the morphology and size of the hierarchical nanostructured nitrogen-doped tungsten trioxide. The size of the primary clusters is 7 ~ 12 μm, and the thickness and length of the nanobelts are 15 ~ 30 nm and 1 ~ 2 μm, respectively.
[0044] N-WO prepared in Example 3 3 −III photocatalyst SEM, such as Figure 3 A and Figure 3 B, and Figure 3 The TEM image shown in C shows that when the molar ratio of sodium tungstate to hydroxylamine hydrochloride is 1:2, N-WO 3 −III photocatalyst has the morphology of hierarchical nanoribbon spherical clusters, HRTEM images, such as Figure 3 D, and XRD patterns, such as Figure 3 As shown in E, it is consistent with N-WO 3 −III has the same 3 The same hexagonal structure as pure WO 3 Compared with the samples, the reduction in the interplanar spacing is due to the influence of N doping. XPS full scan, such as Figure 3 F, and the high-resolution spectrum of the element, such as Figure 3 G and Figure 3 H shows N-WO 3 −III is composed of W, O, and N elements, with the atomic ratio of W / O / N being 25.1:71.1:3.8. 3 −III shows N of type IV 2 The physical adsorption isotherm shows the characteristics of mesoporous materials with typical H3 loops due to the gaps between the nanoribbons, such as Figure 3 I. UV-visible near-infrared absorption spectrum, as shown in Figure Figure 3 J, showing the onset absorption wavelength of the band gap transition (λ onset) is about 488 nm, and there is localized surface plasmon resonance absorption at long wavelengths. Specific surface area ( S BET ) is 24.7 m 2 g ‒1 .
[0045] like Figure 5 As shown in A, N-WO prepared in Example 3 above 3 The average rates of hydrogen and oxygen evolution over the −III photocatalyst were 0.0643 mmol h −1 and 0.0323 mmol h −1 , the ratio of hydrogen evolution to oxygen evolution rate is 1.99. The conversion efficiency of solar energy to hydrogen (STH) for complete photolysis of water is 3.1%. The change of the apparent quantum efficiency (AQE) of complete water splitting with the irradiation wavelength is consistent with the change of UV-visible absorption with wavelength obtained by diffuse reflectance spectroscopy. The production of hydrogen and oxygen is completely consistent with the starting wavelength of light absorption, indicating that the photolysis of water is carried out through interband transitions, such as Figure 5 C. The valence band maximum (VBM) measured by photoelectron spectroscopy (PESA) is 6.37 eV, as shown in Figure 6 As shown in B, N-WO was calculated by UV-visible near-infrared absorption spectroscopy. 3 −III band gap energy of photocatalyst ( E g ) is 2.81 eV ( Figure 6 E), according to the band gap energy ( E g ) and the maximum value of the valence band top (VBM), the minimum value of the conduction band bottom (CBM) is calculated to be 3.56 eV, that is, the potentials of the maximum value of the valence band top (VBM) and the minimum value of the conduction band bottom (CBM) relative to the standard hydrogen electrode are 1.93 V and −0.88 V, respectively, which meet the thermodynamic potential requirements for complete water decomposition, as shown in Figure 6 As shown in F.
[0046] Example 4
[0047] A method for synthesizing a hierarchical nanostructured nitrogen-doped tungsten trioxide catalyst for complete photocatalytic water splitting comprises the following steps: 0.132 to 13.195 g of sodium tungstate dihydrate is fully dissolved in 20 ml of water, then an equal volume of glacial acetic acid is added for thorough mixing, and then 0.084 to 8.340 g of hydroxylamine hydrochloride is added, and the sodium tungstate concentration is 0.01 to 1 mol L −1 , Hydroxylamine hydrochloride concentration: 0.03 ~ 3 mol L −1, and the molar ratio of sodium tungstate to hydroxylamine hydrochloride is maintained at 1:3. The reaction mixture is then transferred to a 50 ml stainless steel autoclave reactor lined with polytetrafluoroethylene, and 4 to 6 pieces of carbon (fiber) paper (1 × 3 ~ 5 × 5 cm) treated with concentrated nitric acid at a concentration of 68 to 70% at 75 °C for 2 hours are placed on a plate. 2 ) is immersed in the reactant solution in the autoclave reactor, sealed and heated to any temperature in the range of 150 ℃ ~ 220 ℃, reacted for 12 hours, and then cooled to room temperature. The carbon (fiber) paper covered with nitrogen-doped tungsten trioxide is taken out, washed three times in warm water at 40 ~ 45 ℃, and dried for use. Thus, nitrogen-doped tungsten trioxide comb-shaped nanobelt spherical clusters with hierarchical nanostructures, namely N-WO 3 −IV catalyst. Hydroxylamine hydrochloride is not only a nitrogen source, but also can effectively control the morphology and size of the hierarchical nanostructured nitrogen-doped tungsten trioxide. The size of the primary spherical clusters is 7 ~ 12 μm, and the thickness and length of the secondary nanobelts are 15 ~ 30 nm and 1 ~ 2 μm, respectively.
[0048] N-WO prepared in Example 4 3 −SEM of IV photocatalyst, such as Figure 4 A and Figure 4 B, and TEM images, as shown in Figure 4 As shown in C, it can be seen that when the molar ratio of sodium tungstate to hydroxylamine hydrochloride is 1:2, N-WO 3 The morphology of the −IV photocatalysts with hierarchical structure comb-shaped nanoribbons and spherical clusters, as shown in the HRTEM image. Figure 4 D, and XRD patterns, such as Figure 4 As shown in G, it is consistent with N-WO 3 −IV has the same 3 The same hexagonal structure as pure WO 3 Compared with the samples, the reduction of the interplanar spacing is due to the influence of N doping. TEM-EDX spectrum, such as Figure 4 E, quantitative analysis and SEM-EDX element distribution diagram, such as Figure 4 As shown in F, N-WO 3 −IV is composed of W, O, and N elements, and the atomic ratio of W / O / N is 25.3:69.8:4.9, and it is proved that W, O, and N are three elements in N-WO 3 −IV is evenly distributed in the photocatalyst, such as Figure 4 F. XPS full scan, such as Figure 4 H, and the high-resolution spectrum of the element, such as Figure 4 I and Figure 4 J shows N-WO 3 −IV is composed of W, O, and N elements, N-WO3 −IV shows N of type IV 2 The physical adsorption isotherms show the characteristics of mesoporous materials with typical H3 loops due to the gaps between the nanoribbons, such as Figure 4 K. UV-visible near-infrared absorption spectrum, such as Figure 4 L shows the onset absorption wavelength of the band gap transition (λ onset ) is about 493 nm, and there is localized surface plasmon resonance absorption at long wavelengths. Specific surface area ( S BET ) is 22.5 m 2 g ‒1 .
[0049] like Figure 5 As shown in A, N-WO prepared in Example 4 above 3 The average rates of hydrogen and oxygen evolution of the −IV photocatalyst were 0.0951 mmol h −1 and 0.0477 mmol h −1 , the ratio of hydrogen evolution to oxygen evolution rate is 1.99. The conversion efficiency of solar energy to hydrogen (STH) for complete photolysis of water is 3.8%. The change of the apparent quantum efficiency (AQE) of complete water splitting with the irradiation wavelength is consistent with the change of UV-visible absorption with wavelength obtained by diffuse reflectance spectroscopy. The production of hydrogen and oxygen is completely consistent with the starting wavelength of light absorption, indicating that the photolysis of water is carried out through interband transitions, such as Figure 5 D. N-WO immersed in water 3 −IV photocatalyst under simulated sunlight irradiation (AM 1.5G 100 mW cm −2 ) A large number of bubbles are precipitated in the water, such as Figure 5 B. The valence band maximum (VBM) measured by photoelectron spectroscopy (PESA) is 6.31 eV, as shown in Figure 6 As shown in A, N-WO was calculated by UV-visible near-infrared absorption spectroscopy. 3 − Band gap energy of IV photocatalyst ( E g ) is 2.78 eV, such as Figure 6 E, according to the band gap energy ( E g ) and the maximum value of the valence band top (VBM), the minimum value of the conduction band bottom (CBM) is calculated to be 3.53 eV, that is, the potentials of the maximum value of the valence band top (VBM) and the minimum value of the conduction band bottom (CBM) relative to the standard hydrogen electrode are 1.87 V and −0.91 V, respectively, which meet the thermodynamic potential requirements for complete water decomposition, as shown in Figure 6 F. N-WO 3The −IV photocatalyst has the most negative conduction band bottom, which accelerates the hydrogen evolution reaction and exhibits the highest complete water splitting activity.
[0050] Table 1: Raw material ratios, product element contents, specific surface areas (SBET), UV-visible near-infrared absorption onset wavelengths (λonset), and solar energy to hydrogen (STH) conversion efficiency values of various N-WO3 photocatalysts prepared in Examples 1-4 of the present invention.
[0051] .
[0052] As can be seen from Table 1, the maximum value of the complete photocatalytic activity of water splitting (solar energy → hydrogen (STH) conversion efficiency) can reach 3.8%.
Claims
1. A method for synthesizing a nitrogen-doped tungsten trioxide complete photolysis water catalyst, comprising the following steps: Step 1: Sodium tungstate and hydroxylamine hydrochloride are fully dissolved in a mixed solvent of water and glacial acetic acid to obtain a solution, wherein the concentrations of sodium tungstate and hydroxylamine hydrochloride in the solution are 0.01 to 1 mol L −1 and 0.0025 ~ 4 mol L −1 , maintaining the molar ratio of sodium tungstate to hydroxylamine hydrochloride in the solution at 1:0.25-4.00, and then transferring to an autoclave reactor; Step 2: immerse 4 to 6 pieces of carbon paper or carbon fiber paper with surface hydroxylation treated with 68 to 70% concentrated nitric acid at 70 to 80°C for 1.5 to 2.5 hours in the reactant solution of the autoclave reactor, seal the reactor and heat it to 120 to 220°C for 5 to 25 hours, cool the reactor to room temperature and release the pressure, take out the carbon paper or carbon fiber paper covered with nitrogen-doped tungsten trioxide with hierarchical nanostructure from the autoclave, wash it with warm water at 40 to 45°C for 2 to 4 times, and dry it at 55-65°C; Step 3: Then place the nitrogen-doped tungsten trioxide carbon paper or carbon fiber paper obtained in step 2 in a vacuum at 4 ~ 6℃min −1 The temperature is heated to 300-400°C at a heating rate and annealed for 1.5-2.5 hours at this temperature to further obtain nitrogen-doped tungsten trioxide that is firmly bonded to carbon paper or carbon fiber paper and has improved crystallinity.
2. The method according to claim 1, characterized in that: When the molar ratio of sodium tungstate to hydroxylamine hydrochloride is 1:0.25-0.4, the prepared hierarchical nanostructured nitrogen-doped tungsten trioxide photocatalyst is a hierarchical structured nanoneedle sea urchin-like cluster, and the loading amount of nitrogen-doped tungsten trioxide on the carbon paper or carbon fiber paper substrate is 2-30 mg cm ‒2 , denoted as N-WO3−I photocatalyst; when the molar ratio of sodium tungstate to hydroxylamine hydrochloride is 1:0.5~1.1, the obtained hierarchical nanostructured nitrogen-doped tungsten trioxide photocatalyst is a spherical cage-like cluster of mutually coiled nanobelts, and the loading amount of nitrogen-doped tungsten trioxide on the carbon paper or carbon fiber paper substrate is 2~30 mg cm ‒2 , denoted as N-WO3−II; when the molar ratio of sodium tungstate to hydroxylamine hydrochloride is 1:1.2~2.1, the obtained hierarchical nanostructured nitrogen-doped tungsten trioxide photocatalyst is a nanobelt spherical cluster, and the loading amount of nitrogen-doped tungsten trioxide on the carbon paper or carbon fiber paper substrate is 2~30 mg cm ‒2 , denoted as N-WO3−III; when the molar ratio of sodium tungstate to hydroxylamine hydrochloride is 1:2.2~4.0, the obtained hierarchical nanostructured nitrogen-doped tungsten trioxide photocatalyst is comb-shaped nanobelt spherical clusters, and the loading amount of nitrogen-doped tungsten trioxide on carbon paper or carbon fiber paper substrate is 2~30 mg cm ‒2 , denoted as N-WO3−IV.
3. The method according to claim 1 or 2, characterized in that: The integrated nitrogen-doped tungsten trioxide carbon paper or carbon fiber paper photocatalyst panel prepared by the synthesis method of step 3 has an area of 1 × 3 ~ 25 × 25 cm 2 .
4. The method according to claim 2, characterized in that: The size of the primary urchin-like nanoneedle clusters of the N-WO3−I photocatalyst is 7 to 10 μm, the diameter of the secondary nanoneedles is 30 to 50 nm, the atomic ratio of nitrogen to tungsten is 1:50 to 25, the light absorption starting wavelength of the N-WO3−I photocatalyst is 460-470 nm, and the solar energy to hydrogen conversion efficiency is 0.5% to 1.6%.
5. The method according to claim 2, characterized in that: The size of the primary cage-like nanobelt cluster of the N-WO3−II photocatalyst is 7 to 12 μm, the width and thickness of the secondary nanobelt are 20 to 30 nm and 5 to 10 nm respectively, the atomic ratio of nitrogen to tungsten is 1:24 to 15, the light absorption starting wavelength of the N-WO3−II photocatalyst is 475-485 nm, and the apparent quantum efficiency value of complete photolysis of water is 1.6% to 2.5%.
6. The method according to claim 2, characterized in that: The thickness and length of the N-WO3-III photocatalyst nanobelt are 5 to 10 nm and 1 to 2 μm, respectively, the atomic ratio of nitrogen to tungsten is 1:14 to 6.6, the light absorption starting wavelength of the N-WO3-III photocatalyst is 485-495 nm, and the apparent quantum efficiency value of complete photolysis of water is 2.5% to 3.1%.
7. The method according to claim 2, characterized in that: The thickness and length of the N-WO3-IV photocatalyst nanobelt are 5 to 10 nm and 1 to 2 μm, respectively, the atomic ratio of nitrogen to tungsten is 1:6.5 to 4.5, the light absorption starting wavelength of the N-WO3-IV photocatalyst is 490-500 nm, and the apparent quantum efficiency value of complete photolysis of water is 3.1% to 4.0%.
8. The method according to any one of claims 1-2, 4-7, characterized in that: In step 1, the volume ratio of water to glacial acetic acid is 1:0.9-1.
1.
9. The method according to any one of claims 1-2, 4-7, characterized in that: In step 1, the volume of the autoclave reactor is 1.125 to 2.5 times the volume of the solution and is lined with polytetrafluoroethylene.
10. The method according to any one of claims 1-2, 4-7, characterized in that: The material of the autoclave reactor is stainless steel.
Citation Information
Patent Citations
Synthesis method of tungsten trioxide
CN103011293A
Method for preparing tungsten photocatalyst heterojunction through doping induction
CN110898827A